Some Properties of Fuzzy Soft Metric Space - Kider, Jehad (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper we introduce the notion fuzzy soft metric space after that we define open fuzzy soft ball, fuzzy soft bounded set, fuzzy soft convergence of sequences, fuzzy soft continuous function from a fuzzy soft metric space to another fuzzy metric space then we study this space and some basic results are investigated.